1995
DOI: 10.1016/0304-3959(94)00278-m
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal steroids to reduce pain after lumbar disc surgery: a double-blind, placebo-controlled prospective study

Abstract: This double-blind, placebo-controlled prospective study investigated whether corticosteroids (beta-methasone) influence residual radicular pain after lumbar disc surgery. The study population consisted of 26 patients undergoing surgery for a herniated lumbar disc at our University Neurosurgical Department. Thirteen patients received beta-methasone intrathecally prior to wound closure, and 13 patients received normal saline. Main outcome measures were pain intensity graded on a 100-mm visual analogue pain scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…in a prospective study of 20 patients undergoing spinal surgery, tai et al (2002) could detect no therapeutic level of cefuroxime in the disc, whereas gentamycin showed a 50% penetration from blood to disc, well within the therapeutic range. Like other researchers (Langmayr et al 1995;rhoten et al 1995), they suggested that high doses of cephalosporins are required to achieve therapeutic levels in the disc. important in this respect are the findings from hoelscher et al (2000) that high doses of antibiotics, including both cephalosporins and aminoglycosides, can have deleterious effects on the survival of cultured disc cells, cell proliferation, and metabolic rates.…”
Section: Postdiscography Discitis (Study V)mentioning
confidence: 89%
“…in a prospective study of 20 patients undergoing spinal surgery, tai et al (2002) could detect no therapeutic level of cefuroxime in the disc, whereas gentamycin showed a 50% penetration from blood to disc, well within the therapeutic range. Like other researchers (Langmayr et al 1995;rhoten et al 1995), they suggested that high doses of cephalosporins are required to achieve therapeutic levels in the disc. important in this respect are the findings from hoelscher et al (2000) that high doses of antibiotics, including both cephalosporins and aminoglycosides, can have deleterious effects on the survival of cultured disc cells, cell proliferation, and metabolic rates.…”
Section: Postdiscography Discitis (Study V)mentioning
confidence: 89%
“…Betamethasone was selected in this study because it has a low mineralocorticoid effect, high anti-inflammatory properties and it is safe for intrathecal use. 18 Various studies showed no significant side effects of intrathecal betamethasone injection, 19 Langmayr et al observed no side effects in patients having lumbar disc surgery and Latham et al showed no pathologic effects in injected sheep with intrathecal betamethasone 5.7mg, but showed neurotoxicity at a dose of 11.4mg. 20 In our study we only injected 2mg of betamethasone which showed no significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,7 In the treatment of chronic pain various studies propose intrathecal administration of steroids. 8,9,10,11 But studies regarding the use of intrathecal administration (which also produces higher local concentration in addition to less side effects 4 ) route as post-operative pain relief are lacking, to which objective our study is directed, as it is the aim of our study to determine the use of intrathecal betamethasone administration as effective postoperative analgesic in gynecologic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Among other substances that have been used intrathecally, in one report betamethasone was administered intrathecally while another report mentions the use of 100 µg neostigmine [85,86].…”
Section: Intrathecal Analgesiamentioning
confidence: 99%